Platelet-rich plasma promotes bone injury repairment in rats with diabetes mellitus - WU Zhigang, QUAN Dong, CHANG Xin, CHEN Xuexue, ZHANG Ziru (Jichu yixue yu linchuang, 2023)
Objective To investigate whether platelet-rich plasma (PRP) can promote osteoblasts differentiation in diabetic mellitus(DM) adipose-derived stem cells(ADSCs) by M2 polarization of DM bone marrow derived macrophages(BMDMs). Methods PRP was extracted from the heart of rats according to the instructions of the kit. BMDMs and ADSCs of DM rats were isolated and cultured, then identified by flow cytometry. BMDMs were divided into control group (PRP 0%) and PRP group (1%, 5%, 10%); ADSCs were divided into: control group (control, ADSCs, 2×105/mL, + same volume as PRP group without PRP plasma), ADSCs+BMDMs group (BMDMs group, 2×105/mL, + plasma without PRP), ADSCs+10% PRP group (PRP group, medium with 10% PRP), and ADSCs+BMDMs+10% PRP group (BMDMs+PRP). Transwell was used to count ADSCs by polarized BMDMs in invasion experiment. The polarization of BMDMs and osteogenic differentiation of ADSCs were determined by RT-qPCR and Western blot. The expression of osteogenic protein Osterix was detected by immunofluorescence. The bone defect model of DM rats was constructed with 3 mm×5 mm at femoral epiphysis, and the rats were divided into: control group (DM rats), ADSCs+ clodronate liposomes (CLP)group (ADSCs group), ADSCs+BMDMs group (BMDMs group without CLP injection), ADSCs+CLP+PRP group (PRP group), ADSCs+PRP group (BMDMs+PRP group without CLP injection). CLP(5 mL/kg) was injected into tail vein of rat 48 hours before operation followed by injection twice a week after surgery for 8 weeks. ADSCs (1×107/mL) and alginate gel mixture were injected into the bone defect, and PRP was treated once every 2 weeks with 500 μL PRP for 4 times. Micro-CT was used to reconstruct and quantitatively analyze the bone defect repair in DM rats. Results The purity of ADSCs positive markers Sca-1 and CD29 were 85.4% and 99.9% respectively and and the purity of BMDMs positive markers CD11b and F4/80 were 94% and 90%. Compared with the control group, BMDMs polarized into M2-type dependent on PRP concentration (P＜0.05). Compared with PRP group, the cell counting of ADSCs migrated in BMDMs+PRP group was significantly increased(P＜0.05). Compared with other groups, the osteogenic differentiation activity and the expressions of osteogenic proteins and genes were significantly increased in ADSCs with BMDMs+PRP treatment(P＜0.05). Bone volume/ tissue volume(BV/TV),trabecular number(Tb.N)and trabecular thickness(Tb.Th)were significantly increased in the BMDMs+PRP group compared with the other groups (P＜0.001). Conclusions PRP promotes ADSCs migration and osteogenic differentiation by stimulating the polarization of BMDMs towards M2 in vitro. BMDMs+PRP can significantly promote the differentiation of ADSCs into osteoblasts and accelerate bone formation in vivo, thus improving the poor healing of diabetic bone defects of rats.